With a mind to kill - Horowitz, Anthony, 1955-; Fleming, Ian, 1908-1964 (A James Bond novel, 2022)
Traveling behind the Iron Curtain, James Bond must convince the Russians, including a beautiful Soviet psychiatric analyst, that he is a double agent to infiltrate a group planning a major act of terrorism, which, if successful, will destabilize relations between the East and West.